UMP, IYRES collaboration in big data technology and youth development - Mimi Rabita, Abdul Wahit (2021)
KUALA LUMPUR, 18 November 2021 - A memorandum of understanding (MoU) for strategic collaboration was signed between the Institute for Youth Research Malaysia (IYRES) and Universiti Malaysia Pahang (UMP) at the Podium Hall, Ministry of Youth and Sports Tower, Putrajaya, today.